Consumer Preferences in Consuming Geprek Chicken products - Pateda, Sry Yenni (Jambura Journal of Animal Science, 2024)
Preference for fried chicken is always increasing, this is proven by the increasing demand for fried chicken. This condition creates different tastes for consumers. The aim of this research was to determine the attributes of fried chicken that are preferred and the factors that influence preference for fried chicken. This research was carried out from February to March 2023. The method used in this research was survey research method, namely collecting primary and secondary data. The sample was determined using incidental sampling, the number of respondents in the study used the Slovin formula with 98 respondents. The data analysis used is descriptive analysis nd chi square analysis. The research results show that the consumer behavior of fried chicken for reasons of purchase obtained a score of 284, frequency of purchase 247, number of portions 250, purpose of purchase 251, all variables were categorized as good. Geprek chicken consumer preferences are not the same, meaning there are differences between the attributes of price, taste, shape, texture and presentation with the respective results X² table 7.815 meaning significantly different. Factors that influence consumer preferences such as location have an average value of 310, information, 247, joint purchasing decisions 253, purchase time 250, availability of fried chicken 246. The results of the continuum line with a score interval of 245-318 indicate the good category